Genetic variability and inter-relation of seed yield with contributing traits in Indian mustard (Brassica juncea) (Journal of Oilseed Brassica, 2026)
The experiments were conducted involving thirty nine genotypes of Indian mustard including 28 F1 crosses and 11 parental genotypes during Rabi 2014-15 to 2015-16 at ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur, India. Analysis of variance on 12 quantitative characters was carried out which revealed considerable amount of genetic variability in genotypes for all the traits. The mean, range, genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability in broad sense and genetic advance were calculated. High genetic advance (GA %) coupled with high heritability for seed yield, 1000-seed weight, siliqua length, plant height and number of primary branches/ plant indicated the effectiveness of selection for these traits. 1000-seed weight, siliqua length, plant height, main shoot length and days to maturity were positively associated with seed yield; hence the selection for these traits would help in improving the seed yield. The crosses NRCHB 101 x NPJ 112, (NPJ 112 x RRN 727) x RH 406 and NPJ 112 x RRN 727 revealed high mean performance for seed yield can be advanced for yield improvement and selection of superior genotypes.